2020
DOI: 10.1093/deafed/enaa015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Vocabulary Intervention on Teaching Multiple-Meaning Words to Students Who Are d/Deaf and Hard of Hearing

Abstract: Building vocabulary knowledge, especially breadth and depth of word meanings, is a crucial step in assisting students to read and comprehend print independently. A large body of research has documented the low reading achievement levels of a number of Deaf and hard-of-hearing (DHH) students. The goal of the present study was to examine the effects of a vocabulary intervention to teach 24 multiple-meaning words to fourth-grade DHH students in Saudi Arabia by utilizing a single-case experimental design (multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Another major challenge that d/Dhh students face is the lack of provision for sign language and subtitles in videos provided by teachers on the Madrasati platform. Several studies have confirmed the importance of using sign language and subtitles during distance education with d/Dhh students to help them easily access content ( Allen et al, 2014 ; Alqraini & Paul, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another major challenge that d/Dhh students face is the lack of provision for sign language and subtitles in videos provided by teachers on the Madrasati platform. Several studies have confirmed the importance of using sign language and subtitles during distance education with d/Dhh students to help them easily access content ( Allen et al, 2014 ; Alqraini & Paul, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lessons with subtitles are not enough. Many d/Dhh students have severely poor reading skills and do not receive an adequate benefit from subtitles ( Alqraini & Paul, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because children with HL and children with NH are growing their vocabularies at similar rates it is unlikely that the children with HL will catch up (Nicholas & Geers, 2007;Nittrouer et al, 2012). As these assessments were only six months apart, it is possible that children with HL will show steeper rates of growth as preschool progresses that would allow them to catch up with their peers with normal hearing, but it is more likely that additional intervention will be needed if vocabulary levels for children with HL are to match those of children with NH (Lund, 2018) (Alqraini & Paul, 2020;Antia et al, 2021;Moeller, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, este trabajo no se ha basado en estudiar la significación que tiene el vocabulario oral, en su generalidad, sobre la comprensión lectora, sino que, por un lado, hace hincapié en el rol predictor que cumple la profundidad, como parte importante del componente léxico-semántico, en el desarrollo lector del alumnado con sordera. Y, por otro lado, guarda una relación intrínseca con la intervención docente, ya que sugiere la búsqueda de variantes metodológicas, para la enseñanza y mejora del nivel lector de los estudiantes con sordera, en las que el conocimiento de vocabulario, y específicamente el profundo, tengan una importante cabida y mayor consideración (Alqraini, 2018;Alqraini y Paul, 2020;Coppens et al, 2013).…”
Section: Discussionunclassified
“…Sobre lo último es importante mencionar que la amplitud, es decir, el número de palabras que una persona puede reconocer (Alqraini y Paul, 2020), ha sido, por un lado, la más estudiada en el alumnado con sordera, y, por otro lado, considerada como un factor clave en la comprensión de textos. Todo ello en menoscabo de la profundidad, poco consolidada de cara al análisis de la influencia que el vocabulario tiene en esta destreza (Anderson y Freebody, 1985;Paul y O'Rourke, 1988) y limitada en las investigaciones hasta las últimas décadas, realmente decisivas para demostrar que no solo influye en los procesos de comprensión lectora del alumnado con sordera, sino que, además, determina estos procesos con un peso mayor del que aporta la amplitud (Leider, Proctor, Silverman y Harris, 2013;Paul, 2003) e influye en el reconocimiento visual de las palabras y su beneficio, por delante de los elementos que componen el Modelo Simple de Lectura o Simple View of Reading, en la comprensión lectora (Paul, 1996).…”
Section: Introductionunclassified